Hepatitis B and C in doctors and dentists in Nigeria (1997)
"We surveyed a random sample (n=75) of doctors and dentists at University College Hospital, Ibadan, Nigeria. They were offered anonymous testing for hepatitis B surface antigen (HBsAg), hepatitis B antibodies to hepatitis B core antigen (anti-HBc) and to hepatitis C virus (anti-HCV) by enzyme immunoassay. The results suggest a high prevelance of hepatitis B virus (HBV) with a high potential of transmissibility, as well as a high prevalence of HCV infection. The majority of the doctors and dentist use universal precaution for protection against viral hepatitis on <50% of the occasion when they carry out procedures on their patients. Infection with HBV was associated with type of specialty (surgeaon, dentists) and lack of HBV vaccination (p<0.05). After logistic regression, these factors, were independently associated. with HBV infection (p<0.05). Sixty (80%) had not hepatitis received prior HBV vaccination. Unvaccinated personnel were more likely to be surgeons, dentists, <37 years of age, and have fewer years of professional activity (p<0.05). After logistic regression, only fewer years of professional activity remained independently associated with lack of vaccination (p<0.05). To reduce the occupational exposure of doctors and dentists use universal precaution must be rigorously adhered to when the doctors and dentists carry out procedures on their procedures on their patients, and all health-care workers should be vaccinated with HBV vaccine and the HCV vaccine, when it becomes available."